Climatoterapia de la cuenca del barranco de La Virgen (Islas Canarias) - Navarro García, Eduardo; Alonso Díaz, Simeona Josefina; San Martín Bacaicoa, Josefina (Anales de Hidrología Médica, 2008)
The Barranco la Virgen it’s a ravine placed between the municipalities of Valleseco and Firgas from Grand Canary Island. Its watershed is deep and covered with endemic vegetation. There are in this zone many springs of mineral waters, as Las Madres, Mayorazgo, El Rapador, San Juan, Los Chorros, Fuente Agria, La Ideal, La Ideal I, La Ideal II, San Antón, etc. In the century XIX the climatology and the most common diseases occurred in the Canary Islands have been analyzed by Pascual Madoz. Climatotherapy also has been studied by others research workers as Gregorio Chil Naranjo 1876, Tomás Zerolo (1884 and 1889), Luis Millares Cubas (1915), Juan Bosch Millares (1932), Antonio Castillo de Lucas 1962, Alejandro-Carlos de Györkö- Györkö (1968). Temperature, pluviometry and atmospheric pressure have been analyzed between1928-2001. The Barranco la Virgen, present a mountain climate with soft middle temperatures, moderate pluviometry and stable atmospheric pressure. Therefore, has been indicated, in convalescents, anemic, pulmonary tuberculosis, chronicle bronchitis, as well as in asthmatics.
Keywords: Barranco la Virgen; Mountain climate; Clinical indications